MicroRNA Targeting to Modulate Tumor Microenvironment - Kuninty, Praneeth R.; Schnittert, Jonas; Storm, Gert; Prakash, Jai (Frontiers in Oncology, 2016)
Communication between stromal cells and tumor cells initiates tumor growth, angiogenesis, invasion, and metastasis. Stromal cells include cancer-associated fibroblasts, tumor-associated macrophages, pericytes, endothelial cells, and infiltrating immune cells. MicroRNAs (miRNAs) in the tumor microenvironment have emerged as key players involved in the development of cancer and its progression. miRNAs are small endogenous non-protein-coding RNAs that negatively regulate the expression of multiple target genes at post-transcriptional level and thereby control many cellular processes. In this review, we provide a comprehensive overview of miRNAs dysregulated in different stromal cells and their impact on the regulation of intercellular crosstalk in the tumor microenvironment. We also discuss the therapeutic significance potential of miRNAs to modulate the tumor microenvironment. Since miRNA delivery is quite challenging and the biggest hurdle for clinical translation of miRNA therapeutics, we review various non-viral miRNA delivery systems that can potentially be used for targeting miRNA to stromal cells within the tumor microenvironment.